2002
DOI: 10.1080/09500340110115488
|View full text |Cite
|
Sign up to set email alerts
|

On the geometry of entangled states

Abstract: The basic question that is addressed in this paper is finding the closest separable state for a given entangled state, measured with the Hilbert Schmidt distance. While this problem is in general very hard, we show that the following strongly related problem can be solved: find the Hilbert Schmidt distance of an entangled state to the set of all partially transposed states. We prove that this latter distance can be expressed as a function of the negative eigenvalues of the partial transpose of the entangled st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 16 publications
2
75
0
Order By: Relevance
“…3 We say a density matrix ̺ has a positive 2 A quantitative study on the shape of these sets in space where the coordinates are the density matrix elements is given in Ref. [48]. 3 Note that this also holds for the full transposition.…”
Section: The Ppt Criterionmentioning
confidence: 99%
“…3 We say a density matrix ̺ has a positive 2 A quantitative study on the shape of these sets in space where the coordinates are the density matrix elements is given in Ref. [48]. 3 Note that this also holds for the full transposition.…”
Section: The Ppt Criterionmentioning
confidence: 99%
“…Proof: We will use similar techniques as used in [12,13,14], where it was shown that surfaces of constant concurrence can be generated by transformingR →R ′ = L 1R L T 2 by left and right multiplication with proper orthochronous Lorentz transformations, taken into account the constraint that the (0, 0) element ofR (representing the trace of ρ) does not change under these transformations. They leave the Lorentz singular values [13] invariant, and the concurrence is a function of these four parameters only.…”
Section: Theorem 2 the Minimal Violation Of The Chsh Inequality For Gmentioning
confidence: 99%
“…In general it is not easy to find the correct state ρ 0 which minimizes the distance (for specific procedures, see, e.g., Refs. [32,33,34]). However, we can use an operator like in Eq.…”
Section: How To Check a Guess Of The Nearest Separable Statementioning
confidence: 99%